Taxonomic and Functional Metrics of Ciliates and Amoeboid Protists in Response to Stream Revitalization - Gulin, Vesna; Vlaičević, Barbara; Sertić Perić, Mirela; Rebrina, Fran; Matoničkin Kepčija, Renata (Frontiers in Microbiology, 2022)
Tufa-depositing streams provide great microhabitat complexity and are therefore inhabited by various periphytic phagotrophic organisms such as ciliates and amoeboid protists. Recent removal of invasive plant species Ailanthus altissima (Mill.) Swinge from the Skradinski buk tufa barrier (Krka National Park, Croatia) resulted in changes in the barrier hydromorphology including the reactivation (revitalization) of dry streams. The objective of this study was to investigate: (1) the taxonomic and functional response of periphytic ciliates and amoeboid protists to stream revitalization by comparing taxonomic (i.e. abundance, species richness and diversity) and functional (i.e. functional diversity) metrics between revitalized (N) and control sites (C) during one- and two-months immersion period; (2) which environmental and (3) periphyton-associated factors shape the taxonomic and functional metrics and to what extent; (4) how duration of immersion affects taxonomic and functional metrics at revitalized sites. Our results showed that taxonomic and functional metrics of ciliates and amoeboid protists responded to the prevailing conditions characteristic of revitalized tufa-depositing streams: changing hydrology (occasional high flow or drought), soil drainage, and extensive inorganic matter, i.e., tufa deposition, although their responses were somewhat different. The two assemblages also showed different responses of taxonomic and functional metrics with respect to immersion duration: while the taxonomic and functional diversity of ciliates at N sites increased with longer immersion, indicating niche diversification, those of amoeboid protists hardly changed with time. Our results suggest that a comprehensive analysis of taxonomic and functional metrics of ciliates and amoeboid protists could be a good proxy for assessing revitalization of tufa-depositing streams. However, the temporal component should always be considered when conducting such studies, as the colonization processes of ciliates and amoeboid protists are quite complex, especially in tufa-depositing streams.